Surgical cure of intractable epilepsy caused by retained intracranial foreign body under cortical electroencephalography monitoring: case report and literature review - Tan, Zhigang; Wang, Ming; Wan, Jingwei; Li, Xinxin; Cui, Yan (Frontiers in Surgery, 2025)
Post-Traumatic Epilepsy is a common and severe complication following brain trauma. However, there are few reports on intractable epilepsy caused by retained foreign bodies. This article reports a case of a patient with a metal foreign body retained in the cranium for 20 years due to trauma, resulting in drug-resistant epilepsy which type is focal to bilateral tonic-clonic seizure. Through preoperative imaging and neurophysiological techniques, the foreign body and epileptogenic zone were precisely located. Intraoperative cortical electroencephalography monitoring was used to accurately remove the foreign body and resect the epileptogenic focus, which pathological result indicates gliosis and calcification. The intractable epilepsy was effectively controlled, and the patient experienced no seizures postoperatively.